Analysis of Implementation of Financial Accounting Standards for Micro, Small and Medium Entities in the Preparation of Financial Statements in MSME Ernov Bali - Ni Luh Sri Utami Baktika; I Made Dana Saputra; I Ketut Suwintana (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2022)
SAK EMKM is a Financial Accounting Standard for Micro, Small and Medium Entities which is made simpler than SAK ETAP. There are 3 financial statements that must be prepared by MSMEs, including statements of financial position, profit and loss, and notes to financial statements. This research uses descriptive qualitative method. This research was conducted for 6 months covering preparation to implementation. The research subjects are owners and employees of MSME Ernov Bali and the object of research is the financial report of MSME Ernov Bali in 2021. Data collection techniques are carried out by interview and documentation. The results showed that MSME Ernov Bali had not fully prepared financial statements in accordance with SAK EMKM. Therefore, it is recommended that MSME Ernov Bali improve its financial statements to make it easier to prepare financial reports.